Effects of intestinal alkaline phosphatase on intestinal barrier function in a cecal ligation and puncture (CLP)‐induced mouse model for sepsis. Issue 3 (21st November 2019) - Plaeke, Philip; De Man, Joris G.; Smet, Annemieke; Malhotra‐Kumar, Surbhi; Pintelon, Isabel; Timmermans, Jean‐Pierre; Nullens, Sara; Jorens, Philippe G.; Hubens, Guy; De Winter, Benedicte Y.
Abstract: Background: Sepsis is a severe pathological condition associated with systemic inflammation, intestinal inflammation, and gastrointestinal barrier dysfunction. Intestinal alkaline phosphatase (IAP) has been demonstrated to detoxify lipopolysaccharide, an important mediator in the pathophysiology of sepsis. We investigated the effect of treatment with IAP on intestinal permeability, intestinal inflammation, and bacterial translocation. Methods: OF‐1 mice were divided into 4 groups (n = 12/group), undergoing either a sham or cecal ligation and puncture (CLP) procedure to induce sepsis. Mice received IAP or a vehicle intraperitoneally 5 minutes prior to the onset of the CLP or sham procedure, which was repeated every 12 hours for two consecutive days. After two days, in vivo intestinal permeability, intestinal inflammation, and bacterial translocation were determined. Key results: CLP‐induced sepsis resulted in significantly more weight loss, worse clinical disease scores, bacterial translocation, and elevated inflammatory cytokines. Intestinal permeability was increased up to 5‐fold ( P < .001). IAP activity was significantly increased in septic animals. Treatment with IAP had no effect on clinical outcomes but reduced the increased permeability of the small intestine by 50% ( P = .005). This reduction in permeability was accompanied by a modified gene expression of claudin‐1 ( P = .025), claudin‐14 ( P = .035), and interleukin 12 ( P = .015). A discriminant analysis showed that treatment with IAP is linked to modified mRNA levels of several tight junction proteins and cytokines. Conclusions and inferences: Treatment with IAP diminished CLP‐induced intestinal barrier disruption, associated with modified expression of several cytokines and claudins. Nevertheless, this effect did not translate into better clinical outcomes in our experimental setup. Abstract : Sepsis is a severe condition associated with intestinal barrier failure, bacterial translocation, and intestinal inflammation. Administration of intestinal alkaline phosphatase partially restored this impaired gastrointestinal barrier in a murine model for sepsis, while influencing several tight junction proteins and cytokines.